Assessment of Early Cardiovascular Risk in Children and Adolescents with Essential Hypertension - Stelcar, Andreja; Homsak, Evgenija; Marcun Varda, Natasa (Klinische Pädiatrie, 2017)
The aim of our study was to investigate some early markers of hypertensive target organ damage in hypertensive children and adolescents, and to detect those showing most prominent clinical significance. We included 100 children with essential hypertension (EH) and 50 age-matched healthy control children, and evaluated left ventricular mass (LVM), intima-media thickness in the carotid arteries (IMT), pulse wave velocity (PWV), microalbuminuria, biochemical parameters and some adipokines. Statistically significant differences between the 2 groups were observed for HDL-cholesterol, LDL-cholesterol, triglycerides, insulin, uric acid, glucose, apolipoprotein A1, and total adiponectin. The mean values of IMT, PWV and LVM were greater in hypertensive children, but only the differences in IMT and LVM were statistically significant. In addition, hypertensive children showed significantly higher values of AoSP (aortic systolic pressure), AoPP (aortic pulse pressure) and AIx@75 (augmentation index corrected for heart rate of 75 b.p.m.). Metabolic syndrome was diagnosed in 31% of hypertensive children. A significant number of children with EH have early target organ changes as well as other risk factors, including metabolic syndrome, especially obese ones. However, IMT, LVM and some parameters of arterial stiffness have been found to be early markers in both obese and non-obese hypertensives. In addition, adipokines and coagulation factors seem to be important in obese hypertensives.
Keywords: adipokines; essential hypertension; intima-media thickness; left ventricular hypertrophy; pulse wave velocity